Analisis Peta Mutu Pendidikan SMA Kabupaten Lombok Tengah Tahun 2020 - Tohar, Mohamad (Jurnal Paedagogy, 2022)
The purpose of this study is to produce a portrait of the educational quality of Central Lombok High School in 2020 through the process of data collection, environmental analysis, as well as recommendations and quality improvement strategies referring to the results of mapping the quality of education in order to be an inspiration for education units and local governments in implementing SPMP. properly and sustainably. The research method used is descriptive qualitative. This research data collection includes 2020 quality report cards sourced from Dapodik (dapodikdasmen.kemdikbud.go.id) and data sourced from PMP (pmp.dikdasmen.kemdikbud.go.id). Based on the results of the analysis of the high school education quality map, it was concluded that none of the senior high schools "Towards SNP 5" or obtained the SNP criteria even though the accreditation status was A, and "Towards SNP 4", with B accreditation as many as eleven schools, "Towards SNP 4" with three schools have C accreditation status, "Towards SNP 2" with C accreditation status of two schools, "Towards SNP 1" with C accreditation status as many as one school. Based on an analysis of the strengths and weaknesses of each indicator to the sub-indicators of each standard, a portrait of the achievement of the SNP is obtained that needs to be recommended to education stakeholders, including quality improvement strategies that can be carried out to improve the performance of education units.